Structural Reforms in Government Bond Markets. (IMF Working Papers; Working Paper ;, 1998)
The paper documents institutional reforms that have taken place in the government debt markets of many industrial countries since the early 1980s, and investigates the impact of three key changes: (i) the move from relationship financing to market funding; (ii) the introduction of options; and (iii) the introduction of futures. Variance ratio tests on bond data for 14 industrial countries indicate that the move to market funding increased the volatility of bond yields and improved the informational efficiency of the secondary markets. The introduction of options and futures increased the informational efficiency of the underlying market, but did not have a stabilizing effect.